The Association of Pre-operative Serum Albumin Levels and Post-operative In-Hospital Death in Patients Undergoing Gastrointestinal Surgeries in Thailand: A Retrospective Cohort Study - Porapong Petch-in; Surasak Saokaew; Pochamana Phisalprapa; Piyameth Dilokthornsakul (Adis, Springer Healthcare, 2023)
Abstract Background Pre-operative hypoalbuminemia is known to predict negative outcomes for patients undergoing major surgeries. However, various cut-off points for starting exogenous albumin have been recommended. Objective This study investigated the association between pre-operative severe hypoalbuminemia, in-hospital death, and length of hospital stay in patients undergoing gastrointestinal surgery. Methods A retrospective cohort study using a database analysis was undertaken on hospitalized patients who underwent major gastrointestinal surgery. The pre-operative serum albumin level was classified into three groups: severe hypoalbuminemia (< 2.0 mg/dL) and non-severe hypoalbuminemia (≥ 2.0-3.4 g/dL) and normal level (3.5-5.5 g/dL). To compare between different cut-offs, a sensitivity analysis using another albumin level classification as severe hypoalbuminemia (< 2.5 mg/dL) and non-severe hypoalbuminemia (≥ 2.5-3.4 g/dL) and normal level (3.5-5.5 g/dL) was applied. The primary outcome was post-operative in-hospital death. Propensity-score adjusted regression analyses were applied. Results A total of 670 patients were included. Their average age was 57.4 ± 16.3 years, and 56.1% were men. Only 59 patients (8.8%) had severe hypoalbuminemia. Overall, a total of 93 in-hospital deaths (13.9%) occurred among all included patients, but there were 24/59 (40.7%) deaths among patients with severe hypoalbuminemia, 59/302 (19.5%) deaths among patients with non-severe hypoalbuminemia, and 10/309 (3.2%) deaths among patients with normal albumin level. The adjusted odds ratio for post-operative in-hospital death comparing patients with severe hypoalbuminemia and patients with normal albumin level was 8.11 (3.31-19.87; p < 0.001), while the odds ratio for in-hospital death comparing patients with non-severe and patients with normal albumin level was 3.89 (1.87-8.10; p < 0.001). A sensitivity analysis showed similar findings, the odds ratio for in-hospital death for severe hypoalbuminemia (cut-off as < 2.5 g/dL) was 7.44 (3.38-16.36; p < 0.001), while the odds ratio for in-hospital death for severe hypoalbuminemia (cut-off as 2.5-3.4 g/dL) was 3.02 (1.40-6.52; p = 0.005). Conclusions Severe pre-operative hypoalbuminemia in patients undergoing gastrointestinal surgery was associated with an increased risk of in-hospital mortality. The risk of death for patients with severe hypoalbuminemia was relatively similar when using different cut-offs such as < 2.0 and <2.5 g/dL.